The gastroprotective action of the oral gel “quertulin” on rats which received adrenalin at background dysbiosis - Levitsky, A. P.; Petrenko, A. A. (Journal of Education, Health and Sport, 2017)
Aim: To determine gastroprotective effectiveness of the oral gel “Quertulin” on rats which received adrenalin at background dysbiosis. Methods: The mucoso-adgesive oral phytogel “Quertulin” (quercetin + inulin + calcium citrate) was used. The dysbiosis was reproduced by lincomycin introduction with water in dose of 60 mg/kg during 5 days. The oral application of adrenalin gel (0,18 mg/kg) made everyday during 10 days. The activities of elastase, urease, lysozyme, catalase and content of malonic dialdehide (MDA) were determined into gastric mucosa. Results: It was established lowering of levels of elastase and MDA, but raise of lysozyme by adrenalin action. The introduction of adrenalin background dysbiosis was raised elastase and urease activities. The oral application of quertulin normalized the levels of elastase, MDA, urease, lysozyme, but raised the activity of catalase. Conclusion: The oral applications of adrenalin has gastroprotective action at the expense of the activity of lysozyme and catalase rise. The oral applications of quertulin make gastroprotective action at introduction of adrenalin background dysbiosis at the expense rise level of antioxidant system and lowering the dysbiosis degree.